Representation of a two-way coupled irrigation system in the Common Land Model - S. Zhang; H. Liang; F. Li; X. Lu; Y. Dai (Hydrology and Earth System Sciences, 2025)
Human land–water management, especially irrigation water withdrawal and use, significantly impacts the global and regional water cycle, energy budget, and near-surface climate. While land surface models are widely used to explore and predict the impacts of irrigation, the irrigation system representation in these models is still in its early stages. This study enhances the Common Land Model (CoLM) by introducing a two-way coupled irrigation module. This module includes an irrigation water demand scheme based on soil moisture deficit, an irrigation application scheme considering four major irrigation methods, and an irrigation water withdrawal scheme that incorporates multiple water source constraints by integrating CoLM with a river routing model and a reservoir operation scheme. Crucially, it explicitly accounts for the feedback between irrigation water demand and supply, which is constrained by available surface water (i.e., runoff, streamflow, reservoir storage) and groundwater. Simulations conducted from 2001 to 2016 at a 0.25° spatial resolution across the contiguous United States reveal that the model effectively reproduces irrigation withdrawals, their spatial distribution, and water source proportions, aligning well with reported state-level statistics. Comprehensive validation demonstrates that the new module significantly improves model accuracy in simulating regional energy dynamics (sensible heat, latent heat, and surface temperature), hydrology (river flow), and agricultural outputs (yields for maize, soybean, and wheat). Application analyses highlight the potential of the enhanced CoLM as a valuable tool for predicting irrigation-driven climate impacts and assessing water use and scarcity. This research offers a pathway for a more holistic representation of fluxes in irrigated areas and human–water interactions within land surface models. It is valuable for exploring the interconnected evolution of climate, water resources, agricultural production, and irrigation activities, while supporting sustainable water management decisions in a changing climate.